2007
DOI: 10.1007/s11136-007-9261-x
|View full text |Cite
|
Sign up to set email alerts
|

Is parental rearing an associated factor of quality of life in adulthood?

Abstract: These results strengthen the empirical notion that favorable parental care may be associated with better quality of life in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
1
25
0
11
Order By: Relevance
“…32 In a previous study investigating the contributions of mental and nutritional aspects to global QoL in adolescence, Sawatsky et al 33 found that 42% of the variance of global QoL scores was explained by satisfaction with self; 30% by mental health; 20% by satisfaction with family environment; 4% by satisfaction with living environment; 3% by physical health; and 0% by satisfaction with friendship. Although our theoretical and analytical approaches are somewhat different from those of the Sawatsky et al study, 33 on one hand, our results are in agreement with their findings about mental health and satisfaction with self as the variables that most account for variance in global QoL scores.…”
Section: Discussionmentioning
confidence: 98%
“…32 In a previous study investigating the contributions of mental and nutritional aspects to global QoL in adolescence, Sawatsky et al 33 found that 42% of the variance of global QoL scores was explained by satisfaction with self; 30% by mental health; 20% by satisfaction with family environment; 4% by satisfaction with living environment; 3% by physical health; and 0% by satisfaction with friendship. Although our theoretical and analytical approaches are somewhat different from those of the Sawatsky et al study, 33 on one hand, our results are in agreement with their findings about mental health and satisfaction with self as the variables that most account for variance in global QoL scores.…”
Section: Discussionmentioning
confidence: 98%
“…Ao contrário, parece que essas famílias abriram espaço para que as adolescentes busquem seus sonhos e se tornem adultos maduros e independentes. Embora estejam longe dos pais, trazem consigo o sentimento de amor e proteção o qual, provavelmente as ajude a enfrentar as vicissitudes de sua escolha (Zimmermann, Eisenmann & Fleck, 2008).…”
Section: Discussionunclassified
“…Por meio do WHOQOL-BREF pode-se perceber pior qualidade de vida devido às condições ambientais (Izutsu, Tsutsumi, Islam, Kato, Wakai, & Kurita, 2006). O estudo de Chen e Yao (2010) observou que o processo de construção da identidade pessoal estava associado a uma boa qualidade de vida; práticas educativas parentais à qualidade de vida dos jovens (Zimmermann, Eisenmann & Fleck, 2008).…”
unclassified
“…Na década de 1990, Darling & Steinberg 1 propuseram um modelo teórico de parentalidade para elucidar e acomodar a relação entre estes dois complexos construtos: estilos e prá-ticas educativas parentais. Segundo a literatura específica sobre o tema, tanto os efeitos do estilo parental como os das práticas educativas parentais parecem ser extremamente importantes nos modelos que estudam o desenvolvimento e a saúde de crianças e adolescentes 3,4,5 .…”
unclassified
“…A dimensão superproteção reúne itens que abarcam comportamentos referentes a um zelo excessivo e desmedido dos pais com os filhos. Esses comportamentos denotam alto grau de intrusão e controle sobre suas vidas, com grande expectativa dos pais quanto ao rendimento escolar e/ou exigên-cia de obediência a regras impostas por eles 4,7,9 .…”
unclassified